2022
DOI: 10.21203/rs.3.rs-1791270/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered basal forebrain function during whole-brain network activity at pre- and early-plaque stages of Alzheimer’s disease in TgF344-AD rats

Abstract: Background: Imbalanced synaptic transmission appears to be an early driver in Alzheimer’s Disease (AD) leading to brain network alterations. Early detection of altered synaptic transmission and insight into mechanisms causing early synaptic alterations would be valuable treatment strategies. This study aimed to investigate how whole-brain networks are influenced at pre- and early-plague stages of AD and if these manifestations are associated with concomitant cellular and synaptic deficits. Methods: To this end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…They were hyperactive in open field tests, indicating disinhibition associated with hippocampal or cortical injury. More recent studies have indicated that high levels of Aβ oligomers in the brain and spatial learning and memory impairments can be detected as early as 4-months in TgF344-AD rats [72][73][74].…”
Section: Tgf344-ad Rat Modelmentioning
confidence: 99%
“…They were hyperactive in open field tests, indicating disinhibition associated with hippocampal or cortical injury. More recent studies have indicated that high levels of Aβ oligomers in the brain and spatial learning and memory impairments can be detected as early as 4-months in TgF344-AD rats [72][73][74].…”
Section: Tgf344-ad Rat Modelmentioning
confidence: 99%